Probing the Effects of the FGFR-Inhibitor Derazantinib on Vascular Development in Zebrafish Embryos - Maria P. Kotini; Felix Bachmann; Jochen Spickermann; Paul M. McSheehy; Markus Affolter (MDPI AG, 2020)
Angiogenesis is a fundamental developmental process and a hallmark of cancer progression. Receptor tyrosine kinases (RTK) are targets for cancer therapy which may include their action as anti-angiogenic agents. Derazantinib (DZB) is an inhibitor of the fibroblast growth factor receptors (FGFRs) 1-3 as well as other kinase targets including vascular endothelial growth factor receptor 2 (VEGFR2), colony stimulating factor-1 receptor (CSF1R) and platelet-derived growth factor beta receptor (PDGFRbeta). This study aimed to investigate the effect of DZB on blood vessel morphogenesis and to compare its activity to known specific FGFR and VEGFR inhibitors. For this purpose, we used the developing vasculature in the zebrafish embryo as a model system for angiogenesis in vivo. We show that DZB interferes with multiple angiogenic processes that are linked to FGF and VEGF signalling, revealing a potential dual role for DZB as a potent anti-angiogenic treatment.